Building strategic infrastructure and managing scarce resources in a context with divergent interests. The transformation of Lake Idro into an artificial basin (1807–1934). Issue 5 (20th October 2022) - Paris, Ivan
ABSTRACT: The completion of infrastructure aiming to meet the 'public interest' often clashes with 'private and local interests'. Such conflicts are one of the main causes of the shortfall in Italian infrastructure, and the ability to manage them is indispensable for works to be completed and opportunities to be maximized. Through a long-term study of the transformation of Lake Idro into an artificial basin, this article focuses on decision-making process and aims to contribute to the debate regarding the completion of infrastructure in a context characterized by divergent interests and scarce natural resources. The objective is to highlight which could be the most effective strategies to be followed as well as the parties (institutional or otherwise) able to best bring the project to completion and manage the infrastructure. Speed of construction and high institutional quality prove to be the pillars upon which the entire decision-making process should be built.